Psychological Analysis of Levels of Communicative Actions Construction - Nataliia Honcharuk; Liana Onufriieva (Психолінгвістика)
On the basis of numeral experimental studies, it is stated that the basic stages of any mental skills formation are physiological and neuropsychological levels. It is proved that physiological support is a complex functional system, which consists in the interaction of individual brain structures and it is an integral system of vital activities of the organism. The neuropsychological level involves the features of the brain organization of the process of communicative interaction. It is shown that the analysis of neuropsychological support of a communicative act enables to realize the essence and mechanisms of communicative processes at the level of brain structures functioning. It is noted that neuropsychological mechanisms, including psychoperceptual, psycholinguistic levels of constructing communicative actions, provide higher levels of the communicative process organization. It is found out that the psychoperceptual level of the communicative actions constructing is the initial stage of communicative interaction, which is represented by social perception as the ability to perceive, understand and shape the impression concerning other people. The theoretical analysis of conceptual approaches to communication research is realized. The direction of communicative actions construction is defined. It is shown that the strategic direction of the communicative functions formation is the need to consider not only the content-based characteristics but also the level ones that determine the sequence and stage-formation of the correction and development work on the formation of communicative skills. On the basis of the research, four basic levels of constructing communicative actions (neuropsychological, psychoperceptual, psycholinguistic and social and psychological) are determined. They allow to prepare psychological work on the development of communicative actions and skills successfully.